Evaluation of anti-inflammatory and analgesic effects on the extracts of different parts of Excoecaria agallocha L. - M. Babuselvam, S. Ravikumar, K.A Mohamed Farook, S. Abideen, M. Peer Mohamed and M. Uthiraselvam (Journal of Applied Pharmaceutical Science)
Scientific evaluated that, anti-inflammatory and analgesic activity of ethanol with water in the ratio of 3:1 extracts were obtained from different parts viz., leaves, seeds and latex of Excoecaria agallocha. The latex was sequentially soxhlated with petroleum ether and methanol dried latex in anti-inflammatory processes and analgesic activity in two concentrations (250 mg/kg and 500 mg/kg). Preliminary phytochemical analysis showed that, presence of alkaloids, flavanoids, saponins were found maximum in the seed extract. Acute inflammatory studies showed that, latex, leaves and seed extracts of both concentration of chosen plant produced significant inhibition of carrageenin induced rat paw edema at 3rd hour (p
Keywords: Paw edema, anti-inflammatory, analgesic activity, Excoecaria agallocha,carrageenan, aspirin.